Celecoxib and sulfasalazine had negative association with coronary artery diseases in patients with ankylosing spondylitis: A nation-wide, population-based case-control study. Issue 36 (September 2016) - Wu, Li-Chih; Leong, Pui-Ying; Yeo, Kai-Jieh; Li, Ting-Yu; Wang, Yu-Hsun; Chiou, Jeng-Yuan; Wei, James Cheng-Chung
Abstract : Abstract: The aim of the study is to assess the effects of celecoxib and sulfasalazine on the risk of coronary artery disease (CAD) in patients with ankylosing spondylitis (AS). Using the claims data of Taiwan National Health Insurance (NHI) database, a nationally representative data that contain the medical records of 23 million Taiwan residents, we randomly selected 1 million cohort from the database, and then we enrolled only patients who were newly diagnosed with AS (n = 4829) between year 2001 and 2010, excluding patients who had CAD (ICD-9- CM codes: 410–414) before the diagnosis of AS (n = 4112). According to propensity score matched 1:2 on age, gender, AS duration, Charlson comorbidity index, hypertension, and hyperlipidemia, 236 and 472 patients were included in the case (AS with CAD) and control (AS without CAD) groups, respectively. We used the WHO defined daily dose (DDD) as a tool to assess the dosage of sulfasalazine and celecoxib exposure. Conditional logistic regression was used to estimate the crude and adjusted odds ratios (ORs) and 95% confidence interval (CI) for the risk of CAD associated with use of sulfasalazine and celecoxib. Among 4112 AS patients, 8.4% (346/4112) developed CAD. CAD in AS patients were positively associated with age of 35 to 65, Charlson comorbidities index (CCI), hypertension, and hyperlipidemia. There was no gender difference between case and control groups. After adjustment for age, gender, CCI, hypertension, and hyperlipidemia, sulfasalazine users with an average daily dose ≥ 0.5 DDD (0.5 gm/day) had negative association with CAD events as compared to sulfasalazine nonusers (OR 0.63; 95% CI, 0.40–0.99, P  < 0.05). NSAIDs, including celecoxib, etoricoxib, but no naproxen and diclofenac were negatively associated with CAD. Celecoxib users, with an average daily dose > 1.5 DDD, were negatively associated with CAD events, compared to celecoxib nonusers (OR 0.34; 95% CI, 0.13–0.89; P  < 0.05). In this 10-year population-based case-control study, 8.4% of AS patients developed CAD. Sulfasalazine usage at an average dose of ≥ 0.5 gm/day demonstrated negative association with CAD events in patients with AS.